From the Punished Body to the Governed Psyche: A Study of the Political Body in the Qajar and Pahlavi Eras - seyed morteza hafezi (رهیافتهای سیاسی و بین المللی)
Extended AbstractIntroduction: According to Michel Foucault, the subject does not possess an inherent or pre-existing nature; rather, it is produced through historical transformations. Foucault sought to demonstrate how individuals, embedded within complex networks of power relations, are shaped under the dominance of such power. Based on this premise, one may ask: from the perspective of Foucault's thought, what relationship exists between the body, the mind, and power during the Qajar and Pahlavi eras? In Foucault's philosophy, the subject and its body undergo transformation through successive phases of power structures—shifting from sovereign power to disciplinary power, and ultimately to governmentality and the emergence of biopower. Throughout this historical progression, the body remains the initial and primary target of repression, torture, and punishment. Gradually, however, the central object of power shifts from the body to the mind. This study aims to explore the transformation of social structures designed to normalize individuals and the transition from a peasant-centered society to a citizen-centered one during the Qajar and Pahlavi periods.Method:This paper draws on key aspects of Foucault’s writings, especially those dealing with “corporeality” and his theories related to the body. Foucault’s conception of the politicized body serves as the theoretical foundation of this research. Building on this framework, the study develops a model for genealogical analysis that explores how power has been exercised over the bodies of political subjects.Results and discussion:During the Qajar period, the king's authority was rooted in a model of sovereign power, wherein dominance was asserted through public displays of violence against the social body. Harsh punishments—such as executions and amputations—functioned as tools to reinforce the absolute power of the monarchy. However, reforms initiated by Abbas Mirza in the 19th century began to shift these power structures, moving away from physical violence toward policies aimed at regulating and disciplining the body. These reforms laid the groundwork for broader transformations under the early Pahlavi regime, which sought to establish a new order through precise and continuous control over its subjects as a means of achieving political legitimacy. The creation of a standing army, the construction of Qasr Prison, and the enactment of restrictive laws served as mechanisms for enforcing discipline. These developments, aligned with the ideology of modernity, fostered a climate of fear and repression that suppressed dissent. However, the collapse of Reza Shah’s regime revealed that disciplinary technologies alone were insufficient to suppress social resistance. During the second Pahlavi period, individual autonomy and freedoms were further eroded, and both the bodies and minds of citizens came under constant surveillance. The regime sought to solidify its legitimacy through various ideological discourses, including appeals to ancient Iranian history, as a means of extending power over cultural and social life. Ultimately, these shifts contributed to the emergence of a surveillance society in which individuals were rendered visible, monitored, and controlled. Violence and repression remained central tools for preserving order and ensuring state security.Conclusion:The discourse of power during the Qajar era began with overt domination over subjects' bodies, exercised through sovereign power and direct violence. In the early Pahlavi period, disciplinary power emerged, introducing more indirect yet systematic forms of bodily control, which paved the way for a new mode of governance. As technologies of power became increasingly sophisticated, both bodies and minds were subjected to institutional and structural violence. By the second Pahlavi period, state power extended its reach beyond physical control, fully encompassing the psychological and emotional lives of its citizens. Through surveillance, ideological narratives, and repressive apparatuses, the regime created a society where individuals were persistently governed, monitored, and regulated in both body and soul.